Temperature response material for adapter sheet, preparation method of temperature response material, adapter sheet containing temperature response material and lithium ion battery
By using a composite material of negative temperature coefficient material and conductive agent in the lithium-ion battery adapter, the problem of poor safety of lithium-ion batteries under short-circuit conditions is solved, rapid fuse and high energy efficiency are achieved, and the battery is improved Safety and service life.
Patent Information
- Application Number
- CN202411561110.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-03
AI Technical Summary
Lithium-ion batteries have poor safety under short-circuit conditions. Although the existing high internal resistance adapter can fuse, it reduces the battery's energy efficiency, resulting in a temperature increase and a shortened service life.
Using composite materials with negative temperature coefficient materials and conductive agents as the functional layer of the adapter, the temperature response characteristics are used to quickly cut off the battery reaction during short circuits, and combining suitable material ratios and particle sizes to improve the thermal response speed and safety. .
While ensuring the battery's energy efficiency, it quickly fuses the adapter to prevent thermal runaway and improves the safety and service life of lithium-ion batteries.
Smart Images

Figure CN119253202A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of lithium-ion batteries, and in particular to a temperature-responsive material for a switching plate, a preparation method thereof, and a switching plate and a lithium-ion battery comprising the same. Background Art
[0002] The inherent volatility of renewable energy restricts the adjustment of energy structure, and efficient and safe energy storage technology is one of the key technologies to promote the development of renewable energy technology market and ensure the energy security of national resources. Lithium-ion batteries have many advantages such as long life, fast start-up and low cost, and are one of the fastest-growing and most mature energy storage technologies.
[0003] However, one of the biggest difficulties of lithium-ion batteries is their poor safety. Under short-circuit conditions, the battery is prone to thermal runaway, fire and explosion. Currently, high-internal resistance adapters with holes or slots are often used to ensure that they can fuse under battery short-circuit conditions and cut off the battery path. For example, CN206022509U discloses a lithium-ion battery adapter with a safety fuse design, including an adapter substrate, a battery connection unit is provided on the adapter substrate, the battery connection unit includes a punched hole, and a welding piece is provided inside the punched hole. The welding piece is connected to the outer arc of the punched hole through a straight-line fuse. However, opening holes or slots will increase the internal resistance of the adapter, reduce the energy efficiency of the battery, cause the battery temperature to rise, and shorten the service life.
[0004] Therefore, how to provide an adapter that can both ensure battery energy efficiency and improve the response speed under battery short-circuit conditions has become a problem that needs to be solved urgently. Summary of the invention
[0005] In order to solve the above technical problems, the present disclosure provides a temperature-responsive material for an adapter and a preparation method thereof, and an adapter and a lithium-ion battery containing the same. The temperature-responsive material for the adapter includes a negative temperature coefficient material and a conductive agent. The combination of the two materials can ensure the battery energy efficiency and accelerate the thermal response speed in practical applications, thereby improving safety and promoting the development of lithium-ion batteries.
[0006] In a first aspect, the present disclosure provides a temperature-responsive material for an adapter, wherein the temperature-responsive material for an adapter comprises a negative temperature coefficient material (referring to a material whose resistivity decreases as temperature increases) and a conductive agent.
[0007] The composite material obtained by the present invention has a negative temperature response characteristic and a high electrical conductivity. In practical applications, on the one hand, it can reduce the total resistance of the entire external circuit of the battery, which is beneficial to the improvement of the battery energy efficiency; on the other hand, under conditions such as battery short circuit, the increase in temperature causes the resistance of the negative temperature coefficient material to decrease, thereby increasing the calorific value of the negative temperature coefficient material, quickly cutting off the battery reaction, and ensuring safety.
[0008] The following are preferred technical solutions of the present disclosure, but are not intended to be limitations of the technical solutions provided by the present disclosure. Through the following technical solutions, the technical objectives and beneficial effects of the present disclosure can be better achieved and realized.
[0009] As a preferred technical solution of the present disclosure, the negative temperature coefficient material includes at least one metal oxide having a spinel structure.
[0010] Preferably, in the metal oxide having a spinel structure, the metal is selected from at least two of Ni, Mn, Co, Fe, Cr, Zn, Cd, Ga, In, Mg, Cu, Ti or Be.
[0011] As a preferred technical solution of the present disclosure, the conductive agent includes carbon-based conductive powder and / or metal conductive powder.
[0012] The carbon-based conductive powder includes, but is not limited to, one or more of carbon powder, graphite, carbon nanotubes, graphene or conductive carbon black; the metal conductive powder includes, but is not limited to, any one or more of aluminum powder, copper powder, and Ni-Mn powder. For example, a combination of graphite and aluminum powder, a combination of aluminum powder and copper powder, a combination of carbon powder, aluminum powder and Ni-Mn powder, etc.
[0013] As a preferred technical solution of the present invention, the mass ratio of the negative temperature coefficient material to the conductive agent is (0.1-1):(1-2), for example, 0.1:1, 0.2:1, 0.4:1, 0.6:1, 1:1, 1:1.5, 0.1:2 or 1:2, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0014] In the present disclosure, a suitable material ratio helps to fully exert the role of the negative temperature coefficient material while ensuring the conductivity of the battery. In addition, a suitable material ratio is also conducive to controlling production costs and improving economic benefits.
[0015] As a preferred technical solution of the present disclosure, the temperature responsive material for the adapter is a combination of carbon powder, aluminum powder and Ni-Mn-O spinel material.
[0016] As a preferred technical solution of the present invention, the mass ratio of the carbon powder, aluminum powder and Ni-Mn-O spinel material is 1:(0.3-1):(0.1-0.5), for example, 1:0.3:0.2, 1:0.8:0.1, 1:0.5:0.8, 1:0.4:0.4 or 1:1:0.3, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0017] The present invention limits specific components and ratios to obtain a temperature-responsive material for an adapter with greater negative temperature strength and faster thermal response speed. When used in an ion system battery, when a short circuit occurs in the ion battery, it can rapidly generate heat within seconds, fuse the adapter, cut off the battery's electronic circuit, and prevent thermal runaway.
[0018] As a preferred technical solution of the present invention, the particle size of the negative temperature coefficient material does not exceed 3000nm, for example, 50nm, 100nm, 200nm, 3000nm, 500nm, 800nm, 1000nm, 1500nm, 2000nm, 2500nm or 3000nm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0019] Preferably, the negative temperature coefficient material is a combination of a negative temperature coefficient material with a particle size of 50-200nm and a negative temperature coefficient material with a particle size of 1000-1500nm, such as a combination of 100nm and 1200nm, a combination of 150nm and 1000nm, a combination of 200nm and 1500nm or a combination of 50nm and 1200nm, etc.
[0020] Preferably, the particle size of the conductive agent does not exceed 3000nm, for example 50nm, 100nm, 200nm, 3000nm, 500nm, 800nm, 1000nm, 1500nm, 2000nm, 2500nm or 3000nm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0021] Preferably, the conductive agent is a combination of a conductive agent with a particle size of 50-200nm and a conductive agent with a particle size of 1000-1500nm, such as a combination of 100nm and 1200nm, a combination of 150nm and 1000nm, a combination of 200nm and 1500nm, or a combination of 50nm and 1200nm.
[0022] The present invention achieves better effect by combining negative temperature coefficient materials and conductive agents with different particle sizes.
[0023] In a second aspect, the present disclosure further provides a method for preparing a temperature responsive material for an adapter, comprising the following steps:
[0024] (1) mixing an additive, a soluble metal salt and a solvent, adjusting the pH, and then subjecting the mixture to a hydrothermal reaction to obtain a sol-gel;
[0025] (2) drying and performing a first heat treatment on the sol-gel obtained in step (1) to obtain an intermediate product;
[0026] (3) The intermediate product obtained in step (2) is mixed with a conductive agent, and subjected to cold pressing, a second heat treatment, and a third heat treatment in sequence to obtain a temperature responsive material for an adapter.
[0027] Preferably, the auxiliary agent in step (1) includes but is not limited to citric acid and ethylene glycol.
[0028] Preferably, the soluble metal salt in step (1) is selected according to the desired spinel structure.
[0029] Preferably, the solvent in step (1) comprises water.
[0030] Preferably, in step (1), the pH is adjusted to 2-4, such as 2, 3 or 4, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0031] Preferably, the drying temperature in step (2) is 90-120°C, such as 90°C, 100°C, 110°C or 120°C, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0032] Preferably, the temperature of the first heat treatment in step (2) is 450-550°C, such as 450°C, 480°C, 500°C or 550°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0033] Preferably, the second heat treatment in step (3) is performed in an inert environment.
[0034] Preferably, the temperature of the second heat treatment in step (3) is 900-1100°C, for example, 900°C, 1000°C or 1100°C, etc.; the time is 25-35s, for example, 25s, 30s or 35s, etc., but is not limited to the listed values, and other values not listed within the above range are also applicable.
[0035] Preferably, the temperature of the third heat treatment in step (3) is 700-850°C, for example, 700°C, 750°C, 800°C or 850°C, etc.; the time is 18-30h, for example, 18h, 20h, 25h or 30h, etc., but is not limited to the listed values, and other values not listed within the above range are also applicable.
[0036] In a third aspect, the present disclosure provides a transfer sheet, which includes a substrate and a functional layer arranged on at least one surface of the substrate, and the material of the functional layer includes the temperature-responsive material for the transfer sheet described in the first aspect, or the temperature-responsive material for the transfer sheet prepared by the preparation method described in the second aspect.
[0037] In the present disclosure, the substrate is a conventional adapter sheet in the prior art, such as a copper adapter sheet or an aluminum adapter sheet.
[0038] The present invention sets a specially made functional layer on the surface of the substrate so that it is connected in parallel with the substrate, thereby increasing the conductive area of the conventional adapter and reducing the body resistance of the conventional adapter, effectively improving the energy efficiency of the battery; at the same time, in a high temperature environment or when the battery is short-circuited, the internal resistance of the adapter described in the present invention will decrease rapidly, increasing the current in the circuit, further increasing the heat generation of the adapter, achieving rapid fusing, and effectively preventing the occurrence of thermal runaway of the battery.
[0039] In the present disclosure, it should be noted that the functional layer may completely cover the surface of the substrate, or may be disposed in the middle section of the substrate surface, and the functional layer may be disposed on only one surface, or may be disposed on both the upper and lower surfaces.
[0040] In addition, the method of loading the functional layer onto the substrate includes, but is not limited to, a coating method or a bonding method.
[0041] As a preferred technical solution of the present disclosure, the ratio of the mass of the functional layer to the flow area of the substrate is (3-1000) g:20 cm 2 , for example 3g:20cm 2 , 10g:20cm 2 、50g:20cm 2 100g:20cm 2 200g:20cm 2 , 500g:20cm 2 ,700g:20cm 2 , 800g:20cm 2 or 1000g:20cm 2 etc., but not limited to the listed values, other values not listed in the range are also applicable, preferably (100-500) g:20cm 2 .
[0042] Preferably, an adhesive layer is further provided between the substrate and the functional layer, and the material of the adhesive layer includes silver paste.
[0043] Preferably, the thickness of the adhesive layer does not exceed 1 mm, for example, 0.1 mm, 0.2 mm, 0.4 mm, 0.6 mm, 0.8 mm or 1 mm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0044] Preferably, the adapter is a positive electrode adapter.
[0045] In a fourth aspect, the present disclosure provides a lithium-ion battery, wherein the lithium-ion battery comprises the adapter sheet as described in the third aspect.
[0046] Generally, a lithium-ion battery includes a shell and a winding core, and the winding core includes a positive electrode sheet and a negative electrode sheet. The adapter sheet described in the present disclosure (an aluminum adapter sheet with at least one functional layer disposed on its surface) is used as a positive electrode adapter sheet, one end of which is connected to the positive electrode sheet, and the other end is connected to the positive electrode column. A conventional pure copper adapter sheet is used as a negative electrode adapter sheet, one end of which is connected to the negative electrode sheet, and the other end is connected to the negative electrode column.
[0047] The lithium-ion battery using the adapter sheet described in the third aspect has the characteristics of fast thermal response speed, high safety, high power, strong adaptability, long cycle life, low cost, simple maintenance, and environmental protection, which promotes the development of large-scale energy storage lithium-ion batteries.
[0048] Compared with the prior art, the technical solution provided by the embodiments of the present disclosure has the following advantages:
[0049] The present invention obtains a composite material with negative temperature response characteristics and high electrical conductivity by compounding a negative temperature coefficient material and a conductive agent. During application, on the one hand, it can effectively reduce the total resistance of the entire external circuit of the battery, avoiding the problems of reduced battery energy efficiency and shortened service life caused by the use of open-hole or slotted high-internal resistance adapters in the prior art; on the other hand, under short-circuit conditions, the internal resistance of the adapter can be rapidly reduced, the current in the circuit can be increased, the heat of the adapter can be increased, rapid fusing can be achieved, and safety can be enhanced. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present disclosure and, together with the description, serve to explain the principles of the present disclosure.
[0051] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0052] Figure 1 It is a schematic diagram of the structure of the adapter obtained in the embodiment of the present disclosure;
[0053] Among them, 1. substrate; 2. functional layer. DETAILED DESCRIPTION
[0054] In order to more clearly understand the above-mentioned objectives, features and advantages of the present disclosure, the scheme of the present disclosure will be further described below. It should be noted that the embodiments of the present disclosure and the features in the embodiments can be combined with each other without conflict.
[0055] In the following description, many specific details are set forth to facilitate a full understanding of the present disclosure, but the present disclosure may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present disclosure, rather than all of the embodiments.
[0056] Example 1
[0057] This embodiment provides a method for preparing a temperature responsive material for an adapter sheet. The preparation method refers to the preparation method in Example 1, and the preparation method includes the following steps:
[0058] (1) 10 g of citric acid and 30 g of ethylene glycol are sequentially added to an aqueous solution of 3 g of manganese nitrate and 3 g of nickel nitrate, and the pH value of the solution is adjusted to 4 with aqueous ammonia to obtain a mixed solution; the obtained mixed solution is subjected to a hydrothermal reaction at 120° C. for 1 h to form a sol-gel;
[0059] (2) drying the sol-gel obtained in step (1) at 120° C. using a blower dryer, and then treating at 500° C. for 2 h, and grinding to obtain an intermediate product powder with a particle size of 200 nm;
[0060] (3) 10 g of the intermediate product powder with a particle size of 200 nm and 20 g of carbon powder with a particle size of 300 nm were mixed, and the mixture was ground and cold pressed in sequence to obtain a first green body;
[0061] (4) The first green body obtained in step (3) is sintered at 1100° C. for 25 seconds, cooled to room temperature, and then treated at 750° C. for 24 hours to obtain a temperature responsive material block for the adapter.
[0062] Example 2
[0063] This embodiment provides a method for preparing a temperature responsive material for an adapter, the method comprising the following steps:
[0064] (1) 10 g of citric acid and 30 g of ethylene glycol are sequentially added to an aqueous solution of 3 g of manganese nitrate and 3 g of nickel nitrate, and the pH value of the solution is adjusted to 4 with aqueous ammonia to obtain a mixed solution; the obtained mixed solution is subjected to a hydrothermal reaction at 120° C. for 1 h to form a sol-gel;
[0065] (2) drying the sol-gel obtained in step (1) at 120° C. using a blower dryer, and dividing it into two parts by weight, treating one part at 500° C. for 2 h, and grinding to obtain an intermediate product powder with a particle size of 200 nm, and treating the other part at 550° C. for 2 h, and grinding to obtain an intermediate product powder with a particle size of 1500 nm;
[0066] (3) 5 g of the intermediate product powder with a particle size of 200 nm, 5 g of the intermediate product powder with a particle size of 1500 nm, 10 g of carbon powder with a particle size of 50 nm, and 10 g of carbon powder with a particle size of 1000 nm were mixed, and the mixture was ground and cold pressed in sequence to obtain a first green body;
[0067] (4) The first green body obtained in step (3) is sintered at 1100° C. for 25 seconds, cooled to room temperature, and then treated at 750° C. for 24 hours to obtain a temperature responsive material block for the adapter.
[0068] Example 3
[0069] This embodiment provides a method for preparing a temperature responsive material for an adapter, the method comprising the following steps:
[0070] (1) 10 g of citric acid and 30 g of ethylene glycol are sequentially added to an aqueous solution of 3 g of manganese nitrate and 3 g of nickel nitrate, and the pH value of the solution is adjusted to 3 with aqueous ammonia to obtain a mixed solution; the obtained mixed solution is subjected to a hydrothermal reaction at 150° C. for 1 h to form a sol-gel;
[0071] (2) The sol-gel obtained in step (1) was dried at 100° C. using a blower dryer, and divided into two parts by weight, one part was treated at 500° C. for 2 h, and then ground to obtain an intermediate product powder with a particle size of 200 nm, and the other part was treated at 550° C. for 2 h, and then ground to obtain an intermediate product powder with a particle size of 1500 nm;
[0072] (3) 0.5 g of the intermediate product powder with a particle size of 200 nm, 0.5 g of the intermediate product powder with a particle size of 1500 nm, 10 g of carbon powder with a particle size of 50 nm, and 10 g of carbon powder with a particle size of 1000 nm were mixed, and the mixture was ground and cold pressed in sequence to obtain a first green body;
[0073] (4) The first green body obtained in step (3) is sintered at 900° C. for 35 seconds, cooled to room temperature, and then treated at 850° C. for 18 hours to obtain a temperature responsive material block for the adapter.
[0074] Example 4
[0075] This embodiment provides a method for preparing a temperature responsive material for an adapter, the method comprising the following steps:
[0076] (1) 10 g of citric acid and 30 g of ethylene glycol are sequentially added to an aqueous solution of 3 g of manganese nitrate and 3 g of nickel nitrate, and the pH value of the solution is adjusted to 3 with aqueous ammonia to obtain a mixed solution; the obtained mixed solution is subjected to a hydrothermal reaction at 140° C. for 1 h to form a sol-gel;
[0077] (2) The sol-gel obtained in step (1) was dried at 100° C. using a blower dryer, and divided into two parts by weight, one part was treated at 500° C. for 2 h, and then ground to obtain an intermediate product powder with a particle size of 200 nm, and the other part was treated at 550° C. for 2 h, and then ground to obtain an intermediate product powder with a particle size of 1500 nm;
[0078] (3) 10 g of the intermediate product powder with a particle size of 200 nm, 10 g of the intermediate product powder with a particle size of 1500 nm, 10 g of carbon powder with a particle size of 50 nm, and 10 g of carbon powder with a particle size of 1000 nm were mixed, and the mixture was ground and cold pressed in sequence to obtain a first green body;
[0079] (4) The first green body obtained in step (3) is sintered at 900° C. for 35 seconds, cooled to room temperature, and then treated at 850° C. for 18 hours to obtain a temperature responsive material block for the adapter.
[0080] Example 5
[0081] This embodiment provides a method for preparing a temperature-responsive material for an adapter. The preparation method refers to the preparation method in Example 3, with the only difference being that in step (3), the added amount of carbon powder with a particle size of 50 nm and the added amount of carbon powder with a particle size of 1000 nm are both 25 g.
[0082] Example 6
[0083] This embodiment provides a method for preparing a temperature responsive material for an adapter. The preparation method refers to the preparation method in Example 4, with the only difference being that in step (3), the added amount of carbon powder with a particle size of 50 nm and the added amount of carbon powder with a particle size of 1000 nm are both 3.35 g.
[0084] Example 7
[0085] This embodiment provides a method for preparing a temperature-responsive material for an adapter. The preparation method refers to the preparation method in Example 1, with the only difference being that in step (3), the carbon powder is replaced by aluminum powder.
[0086] Example 8
[0087] This embodiment provides a method for preparing a temperature responsive material for an adapter, the method comprising the following steps:
[0088] (1) 10 g of citric acid and 30 g of ethylene glycol are sequentially added to an aqueous solution of 3 g of manganese nitrate and 3 g of nickel nitrate, and the pH value of the solution is adjusted to 3 with aqueous ammonia to obtain a mixed solution; the obtained mixed solution is subjected to a hydrothermal reaction at 150° C. for 1 h to form a sol-gel;
[0089] (2) The sol-gel obtained in step (1) was dried at 100° C. using a blower dryer, and divided into two parts by weight, one part was treated at 470° C. for 2 h, and then ground to obtain an intermediate product powder with a particle size of 150 nm, and the other part was treated at 530° C. for 2 h, and then ground to obtain an intermediate product powder with a particle size of 1200 nm;
[0090] (3) 4 g of the intermediate product powder with a particle size of 150 nm, 4 g of the intermediate product powder with a particle size of 1200 nm, 5 g of carbon powder with a particle size of 150 nm, 5 g of carbon powder with a particle size of 1200 nm, 5 g of aluminum powder with a particle size of 150 nm, and 5 g of aluminum powder with a particle size of 1200 nm were mixed, and the mixture was ground and cold pressed in sequence to obtain a first green body;
[0091] (4) The first green body obtained in step (3) is sintered at 1000° C. for 30 seconds, cooled to room temperature, and then treated at 800° C. for 20 hours to obtain a temperature responsive material block for the adapter.
[0092] Embodiments 1-8 of the present disclosure also provide a transfer sheet, and the preparation process thereof includes: independently connecting the temperature-responsive material blocks obtained in Embodiments 1-8 to the upper and lower surfaces of the substrate (the substrate is a pure aluminum positive electrode transfer sheet) through silver paste, and the silver paste is purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., with the item number C140024; the thickness of the formed bonding layer (i.e., silver paste) is 0.5 mm. Specifically, the ratio of the mass of the functional layer to the flow area of the substrate is shown in Table 1. The structural schematic diagram of the transfer sheet obtained in the embodiment is shown in FIG. Figure 1 As shown, it includes a substrate 1 and functional layers 2 respectively arranged on the upper and lower surfaces of the substrate 1.
[0093] Table 1
[0094] <![CDATA[Ratio of functional layer to substrate (g / cm 2 )]]> Example 1 500:20 Example 2 500:20 Example 3 1000:20 Example 4 600:20 Example 5 500:20 Example 6 500:20 Example 7 3:20 Example 8 300:20
[0095] Lithium-ion battery for testing:
[0096] The adapter sheets obtained in Examples 1-8 are respectively installed in lithium-ion batteries. Among them, other components of the lithium-ion battery include:
[0097] Positive electrode sheet: by mass percentage, 85wt% of lithium iron phosphate, 5wt% of polyvinylidene fluoride (PVDF) and 10wt% of acetylene black were mixed with N-methylpyrrolidone (NMP) to obtain a positive electrode slurry; the obtained positive electrode slurry was coated on both sides of an aluminum foil current collector, and a positive electrode sheet was obtained after drying and compacting; wherein the thickness of the positive electrode active layer on each side was 43μm;
[0098] Negative electrode sheet: 85wt% of artificial graphite, 10wt% of sodium carboxymethyl cellulose (CMC) and 5wt% of conductive graphite are mixed with water in percentage by mass to obtain a negative electrode slurry; the obtained negative electrode slurry is coated on both sides of a copper foil current collector, and a negative electrode sheet is obtained after drying and compacting; wherein the thickness of the negative electrode active layer on each side is 45μm;
[0099] Diaphragm: Polypropylene membrane is used as the diaphragm with a porosity of 40%;
[0100] Electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (EDC) were mixed in a volume ratio of 1:1:1, and then 1 mol / L of LiPF was added. 6 Mix well to prepare electrolyte;
[0101] The positive electrode sheet, negative electrode sheet and separator are wound to prepare lithium-ion battery cells, and then a 280Ah lithium-ion battery is obtained after baking, liquid injection, formation and packaging.
[0102] Comparative Example 1
[0103] This comparative example provides a pure aluminum adapter and a lithium-ion battery comprising the same. The lithium-ion battery is the same as Example 1 in all parts except the adapter.
[0104] The adapter sheets obtained in Examples 1-8 and the pure aluminum adapter sheet of Comparative Example 1 were tested, and the specific test conditions were as follows:
[0105] 1. AC internal resistance test
[0106] Test method: The internal resistance of the adapters obtained in Examples 1-8 and the pure aluminum adapter described in Comparative Example 1 was tested at 1000 Hz using an electrochemical workstation. The test results are shown in Table 2.
[0107] Table 2
[0108]
[0109]
[0110] From the results in Table 2, it can be seen that the application of the temperature-responsive material for the adapter sheet disclosed in the present invention can effectively reduce the resistance of the conventional adapter sheet and improve the energy efficiency of the battery; and the effect can be enhanced by further controlling the material composition, ratio and particle size. By comparing Example 2 with Example 1, it can be seen that the use of a composite particle size can reduce the internal resistance more significantly than a single particle size; by comparing Example 5 with Example 3, it can be seen that in the resulting composite material, the amount of conductive agent added is too large, which means that the amount of negative temperature coefficient material added is too small, resulting in the negative temperature response characteristics cannot be fully exerted, the internal resistance is limited, and the adapter sheet cannot be quickly fused under short-circuit conditions; by comparing Example 6 with Example 4, it can be seen that in the composite material, the amount of conductive agent added is too small. Although the AC internal resistance is reduced a lot, its conductivity cannot be guaranteed.
[0111] 2. Short circuit test
[0112] Test method: A short-circuit test machine was used with a wiring resistance of 2.4 milliohms to test the performance of Examples 1-8 and Comparative Example 1 under short-circuit conditions. The test results are shown in Table 3.
[0113] Table 3
[0114]
[0115]
[0116] In summary, the present invention obtains a composite material with both negative temperature response characteristics and high electrical conductivity by compounding a negative temperature coefficient material and a conductive agent. During the application process, on the one hand, it can effectively reduce the internal resistance of the adapter to below 0.28mΩ, thereby improving the energy efficiency of the battery; on the other hand, under short-circuit conditions, it can also rapidly reduce the internal resistance of the adapter, increase the current in the circuit, increase the heat of the adapter, achieve rapid fusing, and enhance safety.
[0117] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "include..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0118] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A temperature responsive material for an adapter, characterized in that: The temperature response material for the adapter includes a negative temperature coefficient material and a conductive agent.
2. The temperature responsive material for the adapter according to claim 1, characterized in that: The negative temperature coefficient material includes at least one metal oxide having a spinel structure; Preferably, in the metal oxide having a spinel structure, the metal is selected from at least two of Ni, Mn, Co, Fe, Cr, Zn, Cd, Ga, In, Mg, Cu, Ti or Be.
3. The temperature responsive material for a transfer sheet according to claim 1 or 2, characterized in that: The conductive agent includes carbon-based conductive powder and / or metal conductive powder.
4. The temperature responsive material for a transfer sheet according to any one of claims 1 to 3, characterized in that: The mass ratio of the negative temperature coefficient material to the conductive agent is (0.1-1):(1-2).
5. The temperature responsive material for a transfer sheet according to any one of claims 1 to 4, characterized in that: The temperature responsive material for the adapter is a combination of carbon powder, aluminum powder and Ni-Mn-O spinel material.
6. The temperature responsive material for the adapter according to claim 5, characterized in that: The mass ratio of the carbon powder, the aluminum powder and the Ni-Mn-O spinel material is 1:(0.3-1):(0.1-0.5).
7. The temperature responsive material for a transfer sheet according to any one of claims 1 to 6, characterized in that: The particle size of the negative temperature coefficient material does not exceed 3000nm; Preferably, the negative temperature coefficient material is a combination of a negative temperature coefficient material with a particle size of 50-200 nm and a negative temperature coefficient material with a particle size of 1000-1500 nm; Preferably, the particle size of the conductive agent does not exceed 3000 nm; Preferably, the conductive agent is a combination of a conductive agent with a particle size of 50-200 nm and a conductive agent with a particle size of 1000-1500 nm.
8. A method for preparing the temperature responsive material for a transfer sheet according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) mixing an additive, a soluble metal salt and a solvent, adjusting the pH, and then subjecting the mixture to a hydrothermal reaction to obtain a sol-gel; (2) drying and performing a first heat treatment on the sol-gel obtained in step (1) to obtain an intermediate product; (3) mixing the intermediate product obtained in step (2) with a conductive agent, and sequentially subjecting the mixture to cold pressing, a second heat treatment, and a third heat treatment to obtain a temperature responsive material for an adapter; Preferably, the auxiliary agent in step (1) comprises citric acid and ethylene glycol; Preferably, the solvent in step (1) comprises water; Preferably, step (1) adjusts the pH to 2-4; Preferably, the temperature of the hydrothermal reaction in step (1) is 120-300°C; Preferably, the drying temperature in step (2) is 90-120°C; Preferably, the temperature of the first heat treatment in step (2) is 450-550°C; Preferably, the second heat treatment in step (3) is performed in an inert environment; Preferably, the temperature of the second heat treatment in step (3) is 900-1100° C. and the time is 25-35 seconds; Preferably, the temperature of the third heat treatment in step (3) is 700-850° C. and the time is 18-30 hours.
9. A transfer sheet, characterized in that: The adapter sheet comprises a substrate, and a functional layer disposed on at least one surface of the substrate, wherein the material of the functional layer comprises the temperature responsive material for the adapter sheet according to any one of claims 1 to 7, or the temperature responsive material for the adapter sheet prepared by the preparation method according to claim 8; Preferably, the ratio of the mass of the functional layer to the flow area of the substrate is (3-1000) g:20 cm 2 , preferably (100-500) g:20cm 2 ; Preferably, an adhesive layer is further provided between the substrate and the functional layer; Preferably, the thickness of the adhesive layer does not exceed 1 mm; Preferably, the adapter is a positive electrode adapter.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the adapter sheet as claimed in claim 9.
Citation Information
Patent Citations
NTC heat-sensitive semiconductive ceramic capable of low-temperature melting and method of manufacturing the same
CN101108773A
Lithium ion battery anode pole piece as well as preparation method thereof and battery using pole piece
CN106784617A
Strain sensor with temperature compensation function and composite material of strain sensor
CN108627080A
Method of producing a NTCR sensor
CN110799667A
NTC thermal sensitive ceramic material suitable for room-temperature and low-temperature zones and preparation method thereof
CN111574200A
